THE TRANSITION FROM EXPLOSIVE TO EFFUSIVE ERUPTIVE REGIME: THE EXAMPLE OF THE 1912 NOVARUPTA ERUPTION, ALASKA - Adams N.K.; Houghton B.F.; Fagents S.A.; Hildreth W. (My University, 2006)
The shift from explosive to effusive silicic volcanism seen in many historical eruptions reflects a change in the style of degassing of erupted magma. This paper focuses on such a transition during the largest eruption of the twentieth century, the 1912 eruption of Novarupta. The transition is recorded in a dacite block bed, which covers an elliptical area of 4 km2 around the vent. Approximately 700 studied blocks fall into four main lithologic categories: (1) pumiceous, (2) dense, (3) flow-banded dacites, and (4) welded breccias. Textural analyses of the blocks indicate portions of the melt underwent highly variable degrees of outgassing. Vesicle populations show features characteristic of bubble coalescence and collapse. A decrease in measured vesicularity and increased evidence for bubble collapse compared with pumice from earlier Plinian episodes mark the transition from closed- to open-system degassing. Block morphology and textures strongly suggest the magma was first erupted as a relatively gas-rich lava dome/plug, but incomplete out-gassing led to explosive disruption. Heterogeneous degassing of ascending magma began in Plinian Episode III and resulted in instability during Episode IV dome growth and a (series of) Vulcanian explosion(s). Modeling of the dynamics of explosion initiation and ejecta dispersal indicates that a significant concentration in gas is required to produce the explosions responsible for the observed block field dispersal. The amount of gas available in the hot pumiceous dome material appears to have been inadequate to drive the explosion(s); therefore, external water most likely contributed to the destruction. © 2006 Geological Society of America.
Keywords: BUBBLE COLLAPSE; DECOUPLED DEGASSING; LAVA DOMES; MICROTEXTURES; NOVARUPTA 1912; PLUGS; VESICLES